Nuclear loads and nuclear shielding performance of EU DEMO divertor: A comparative neutronics evaluation of two interim design options. (May 2020) - You, J.H.; Villari, R.; Flammini, D.; Marzullo, D.; Mazzone, G.
Highlight: A first systematic neutronics study for the European DEMO divertor is reported. Results of extensive assessment of nuclear loading features are presented for two optional design concepts, namely, dome and shielding liner including minor geometrical variants. It was found that both the dome and shielding liner were able to significantly reduce the nuclear loads in the cassette body and the vessel. The maximum damage dose at the end of the lifetime remained subcritical for the cassette body for both cases whereas it locally exceeded the limit for the vessel under the dome. The damage in the vessel could be reduced below the limit either by increasing the dome size or by deploying the shielding liner. The most critical feature was the excessive damage occurring in the own body of the shielding components where the maximum damage dose in the steel heat sink of the dome and the shielding liner far exceeded the design limit at the end of the lifetime. Abstract: In a demonstrational fusion power plant (DEMO), divertor is supposed to protect vacuum vessel and superconducting magnets against neutron flux in the bottom region of the vessel. The vessel is subject to a strict design limit in irradiation damage dose and the magnets in nuclear heating power, respectively. Thus, the DEMO divertor must have the capability to protect sufficiently the vessel and the magnets against neutron flux being substantially stronger than in ITER. In this paper, a first systematic neutronics study for the European DEMO divertor is reported. Results of the extensive assessment of key nuclear loading features (nuclear heating, irradiation damage & helium production) are presented for two optional concepts, namely, dome and shielding liner including minor geometrical variants. The shielding performance of the two competing design options is discussed together with the case of a bare cassette (no shielding), particularly in terms of damage dose compared with the design limits specified for the European DEMO. It was found that both the dome and shielding liner were able to significantly reduce the nuclear loads in the cassette body and the vessel. The maximum damage dose at the end of the lifetime remained subcritical for the cassette body for both cases whereas it exceeded the limit for the vessel under the dome, but only locally on the surface underneath the pumping duct. But, the damage could be reduced below the limit for the vessel by increasing the size of the dome or by deploying the shielding liner. The most critical feature was the excessive damage occurring in the own body of the shielding components where the maximum damage dose in the steel heat sink of the dome and the shielding liner far exceeded the design limit at the end of the lifetime.